Neurological Symptoms as (Post) Pandemic Burden in Children and Adolescents-Single Tertiary Center Experience from Croatia - Trbojević, Tena; Kovačević, Ana; Kukuruzović, Monika; Šeparović, Iva; Bašić Kes, Vanja; Malenica, Maša (Iranian Journal of Child Neurology, 2026)
Objectives: Although COVID-19 primarily affects the respiratory system, the central and peripheral nervous system may be involved. Neurological manifestations of COVID-19 infection occur in acute or post-acute stages and may persist as long-lasting symptoms known as “long-COVID“ or “post-COVID-19”. This study aimed to investigate the clinical profile, outcomes, and management of neurological manifestations after COVID-19 infection in children. Materials & Methods: A retrospective chart review was conducted of all pediatric patients admitted to our tertiary pediatric center with neurological symptoms following COVID-19, meeting criteria for long COVID-19/post-COVID-19, from December 2020 through the end of 2021, with a one-year follow-up period. Results: Eighty-four patients were included (median age 12.7 years; range, 0.5-18 years). Girls were more affected than the boys (female n = 51; 60.7%, χ2 = 3, 86; p = 0,049). The most common neurological manifestation were headache (n = 47; 55.95%), dizziness (n = 19; 22.6%), visual disturbances (n = 9; 10.7%), afebrile seizures (n = 6; 7.1%), and anosmia/hyposmia (n = 4; 4.7%). Overall, 19 (22.6%) patients required psychological support, of whom 4 (4.8%) patients required psychiatric consultation due to suspected mental disorder. The most significant number of patients with neurological symptoms after COVID-19 was observed between October 2020 and March 2021 (n=44, 52.4%). Conclusion: The obtained findings align with the results from similar studies and show that neurological manifestations after COVID-19 infection appear more frequently in school-aged children, predominantly in female patients. Neurological post-COVID-19 symptoms require medical attention to exclude more severe conditions.